Elaboración de salchichas artesanales utilizando harina de trupillo (Prosopis juliflora) como extensor proteico (2020)
The high protein content has turned legumes into a raw material of interest in the formulation of different agro-industrial products. The present investigation determined the technical and economic feasibility of making sausages at an artisanal level using trupillo flour (Prosopis juliflora) as a protein extender. The experimental development consisted of three phases, i) obtaining and bromatological and functional characterization of leaf flours and trupillo seeds, ii) search and standardization of formulations for artisan sausages using trupillo flour as a protein source, and iii) bromatological characterization, sensory evaluation and cost estimation of processed sausages. The flours obtained kept the smell and color of each raw material. Based on the bromatological and functional analysis of the flours, the seed flour was chosen to be included in the sausages, because it showed better protein content (27.7%), ashes (8.04%), swelling capacity (16.77 ml water / g sample), water absorption (7.89g water / g sample) and water holding capacity (27.95 g water / g sample). Three sausage formulations were made: Formulation C (100% wheat flour), Formulation CT (50% wheat flour and 50% trupillo flour) and Formulation T (100% trupillo flour). The sausages presented notable changes in color and texture; Formulation T presented a higher percentage of protein (13.7%). However, formulation C was chosen in the sensory test as the largest accepted by consumers. Considering the nutritional properties of sausages, they could be included in the human diet. However, the consumer's culture regarding the rejection or preference of certain foods is a key factor to improve in order to achieve greater acceptance of the product.